Dark Jokes dalam komunikasi: Studi semiotika Roland Barthes - Arnold Wilson; Daniel Susilo; Alfred Pieter Menayang (SOSIOHUMANIORA: Jurnal Ilmiah Ilmu Sosial dan Humaniora, 2025)
The spread of dark jokes through social media such as Twitter, TikTok, and Instagram has increased significantly. Differences in individual characteristics such as age, gender, trauma experience, and intensity of social media use also shape subjective perceptions and meanings of dark jokes. This study uses a qualitative approach with Roland Barthes' semiotic analysis method to reveal the layers of denotative and connotative meanings of dark jokes in Tretan Muslim video content. Data were obtained through observation of content on Instagram and YouTube, then analyzed with two main stages in Barthes' framework, namely identification of the sign system (signifier and signified) and exploration of myths or ideologies that form dominant meanings. The findings of this study indicate that dark jokes in Tretan Muslim video content not only function as entertainment, but also represent socio-political criticism through a system of layered signs. At the connotative level, the humor becomes a means of demythologizing dominant ideologies such as nepotism, institutional inequality, and hegemony of power, which are packaged symbolically through irony, hyperbole, and intertextuality so that they can be accepted by the wider public.